2005
DOI: 10.1124/jpet.105.088674
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the Ultraviolet B-Mediated Skin Photoaging by a Nuclear Factor κB Inhibitor, Parthenolide

Abstract: The skin photoaging is characterized by keratinocyte hyperproliferation and degradation of collagen fibers, causing skin wrinkling and laxity and melanocyte proliferation that leads to pigmentation. UV is considered to be a major cause of such skin changes. It is well established that nuclear factor B (NF-B) is activated upon UV irradiation and induces various genes including interleukin-1 (IL-1), tumor necrosis factor ␣ (TNF␣), and matrix metalloprotease-1 (MMP-1). It is also known that basic fibroblast growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 42 publications
3
54
0
3
Order By: Relevance
“…Acute exposure to UVB triggers NF-κB system in keratinocytes and skin fibroblasts. NF-κB inhibitors can suppress the changes evoked by UV light in skin, which supports the role of NF-κB system in the photoaging process [36].…”
Section: Nf-κb Pathway: Sensor Of Stress and Immune Insultssupporting
confidence: 58%
“…Acute exposure to UVB triggers NF-κB system in keratinocytes and skin fibroblasts. NF-κB inhibitors can suppress the changes evoked by UV light in skin, which supports the role of NF-κB system in the photoaging process [36].…”
Section: Nf-κb Pathway: Sensor Of Stress and Immune Insultssupporting
confidence: 58%
“…(Saliou et al, 1999;Kim et al, 2001;Wenk et al, 2004). In previous study, it is also reported that UVB-mediated skin photoaging is prevented by suppression of NF-κB activation (Adhami et al, 2003;Tanaka et al, 2005Tanaka et al, , 2007. Thus, inhibition of the NF-κB activation pathway is important for the UVB-mediated skin damage.…”
Section: Suppressive Effect Of Cordycepin On Uvb-induced Nf-κb Activamentioning
confidence: 85%
“…These cellular processes are related to photoaging and photocarcinogenesis [12,13]. UV-mediated DNA damage is mainly attributed to the formation of cyclobutane pyrimidine dimers (CPDs) between adjacent thymine (T) or cytosine (C) residues, or to a lesser extent, formation of pyrimidine (6-4) pyrimidone photoproducts (6-4PPs) via direct absorption of UV photons by the DNA bases [14,15].…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%